Herbivores - Shields, Vonnie D. C. (IntechOpen, 2017)
This book provides an overview of the current knowledge of herbivory. This book contains chapters from a wide variety of topics that fall into the following broad sections: (I) "Plant Defense Mechanisms and Herbivore Adaptations," (II) "Herbivory and Food Processing of Grazing Animals," and (III) "Herbivory Effects on Plant Communities." More specifically, the contributions of this book, written by experts in their respective fields, focus on topics including the chemical plant defense against herbivores as well as herbivore adaptions to plant cyanide defenses, the utilization of biomarkers to study grazing behavior of ruminants, modeling for describing ruminant herbivory, as well as improving grain processing to improve dairy cow performance. Contributions on positive indirect interactions in marine herbivores and algae are included, as is one focusing on herbivory by lizards. These chapters represent recent contributions showing the diversity of ongoing research in this field of study. This book targets a wide audience of general biologists as well as botanists, ecologists, and zoologists including both teachers and students in gaining a better appreciation of this rapidly growing field.